2018
DOI: 10.1177/2325967118796469
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Use and Perception of Internet-Based Orthopaedic Sports Medicine Resources

Abstract: Background:Current research is sparse regarding how patients with orthopaedic injuries perceive and use internet-based information resources.Hypothesis:The majority of patients use the internet to research their orthopaedic condition and are receptive to guidance from their provider.Study Design:Cross-sectional study.Methods:A total of 213 patients attending a sports medicine clinic on the East Coast of the United States were asked to complete a questionnaire regarding their use of internet-based information. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“… 36 Most orthopaedic patients were skeptical of information found online (68%) and would welcome surgeon's guidance on which internet sources to use (83%). 37 Furthermore, most continue to prefer verbal communication with their surgeon to learn about their condition. 36 As a supplement to communication with their surgeon, however, more preferred a website as opposed to a paper handout.…”
Section: Discussionmentioning
confidence: 99%
“… 36 Most orthopaedic patients were skeptical of information found online (68%) and would welcome surgeon's guidance on which internet sources to use (83%). 37 Furthermore, most continue to prefer verbal communication with their surgeon to learn about their condition. 36 As a supplement to communication with their surgeon, however, more preferred a website as opposed to a paper handout.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of misinformation is of particular concern to spine surgeons, as 54% of patients report researching their condition before consultation with orthopaedic or neurosurgical surgeons. 7 Cervical spondylosis is fairly common, with approximately 50% of patients over 40 years old and 85% of patients over 65 years old having some evidence of cervical degeneration. 8,9 Though many patients remain asymptomatic, 8,10 roughly 83 per 100 000 individuals will develop cervical radiculopathy every year.…”
Section: Introductionmentioning
confidence: 99%
“…Aslam et al 7 observed that parents frequently use internet based information before pediatric orthopedic consultations. Koenig et al 8 observed that 54% patients read internet information about their condition while 32% surfed for surgeons before their visit. They found that most patients were either neutral toward or did not trust the internet-based information.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was designed using the metrics that had used before and had been found to be reliable in another outpatient orthopedic patient group. 8 Patients were recruited by and provided consent to the independent study coordinator. The patient filled the questionnaire prior to meeting the surgeon before their proposed TKR operation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation